Complex appreciation of agrotechnikal factors of sweet corn (Zea Mays L. convar. saccharata Koern.) - Lente, Ádám (Acta Agraria Debreceniensis, 2010)
Three agrotechnical factors (sowing time, fertilization, plant density) and the effect of two different genotypes on the yields of sweet corn was studied, in the dry and warm crop-year of 2009 on a chernozem soil in the County of Hajdúság. The experiments were carried out on the Látókép Research Station of Debrecen University. The experiment involved two sowing times (21 of April and 19 of May), six fertilizer levels (control, N30+PK, N60+PK, N90+PK, N120+PK, N150+PK) and two genotypes (Jumbo, Enterprise). Four plant density levels, 45 thousand ha-1, 55 thousand ha-1, 65 thousand ha-1 and 75 thousand ha-1 were used. In the early sowing time the highest yield was obtained with 65 thousand ha-1 plant density level and N120+PK treatment of Jumbo (18169 kg ha-1), while the maximum yield of Enterprise was 17818 kg ha-1 with 75 thousand ha-1 plant density level and N90+PK dose. In case of the late sowing time both hybrids gave the highest yield with 75 thousand ha-1 plant density level and N30 +PKtreatment, with a crop yield of 13143 kg ha-1 (Jumbo) and 14324 kg ha-1, ( Enterprise).